The relationship between social media addiction and psychological symptoms in university students - Karadağ, Atahan; Akçınar, Berna (Journal of Dependence, 2019)
Objective: This study investigates the predictive effects of social media usage, parental attitudes and levels of mindfulness on the depression, obsessive compulsive disorders (OCD) and somatization symptoms in 18-26 year old university students.Method: The study was conducted with 292 undergraduate students mainly studying in Istanbul, Ankara, Antalya and various cities. Demographic and socioeconomic form, social media addiction scale, fear of missing out scale, brief symptom inventory and mindful attention awareness scale was used in this study. Results: The results indicate that 2% of participants have high; 18% have average levels, 47% have low levels of social media addiction. The analyses show that social media usage and the level of mindfulness have an association with the students' level of depression, obsessive compulsive disorders and somatization symptoms.Conclusion: Students who had high levels of social media addiction and low levels of mindfulness were more prone to show psychological symptoms. Results pinpoint the importance of mindfulness in people considering the high usage of social media.
Keywords: Social media; depression; somatization; mindfulness